2015
DOI: 10.1111/jace.13859
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Solid Solution with Rutile‐Type Structure in SiO2–GeO2 System at 12 GPa and 1600°C

Abstract: High pressure and temperature synthesis of compositions made of (Si1−x,Gex)O2 where x is equal to 0, 0.1, 0.2, 0.5, 0.7, and 1 was performed at 7–12 GPa and 1200–1600°C using a Kawai‐type high‐pressure apparatus. At 12 GPa and 1600°C, all the run products were composed of a single phase with a rutile structure. The lattice constants increase linearly with the germanium content (x), which indicates that the rutile‐type phases in the SiO2–GeO2 system form a complete series of solid solutions at these pressure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We loaded amorphous GeO 2 (a-GeO 2 [47]) (three independent loadings), polycrystalline quartzlike GeO 2 (q-GeO 2 ) (two independent loadings), and rutilelike GeO 2 (r-GeO 2 , [48]) (one loading) into diamond anvil cells (DACs). r-GeO 2 was measured at high pressure as a reference material of CN ¼ 6.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…We loaded amorphous GeO 2 (a-GeO 2 [47]) (three independent loadings), polycrystalline quartzlike GeO 2 (q-GeO 2 ) (two independent loadings), and rutilelike GeO 2 (r-GeO 2 , [48]) (one loading) into diamond anvil cells (DACs). r-GeO 2 was measured at high pressure as a reference material of CN ¼ 6.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…Although numerous studies also reported the ADL synthesis and characterization of silicate or borate glasses and melts (for instance, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] ) the strong volatility of some chemical components [48][49][50] (e.g., B 2 O 3 and alkali oxides) under laser irradiation still represents a major drawback of ADL-driven materials discovery, limiting its applicability within these chemical domains. Borate and silicate glasses can be easily prepared by conventional melt-quenching, but ADL was recently shown to provide a superior approach to elucidate transition metal saturation and homogenous nucleation in aluminosilicate glasses and glass-ceramics, [51][52][53] again taking advantage of the high melting temperatures, fast cooling rates and suppression of heterogeneous surface nucleation.…”
Section: Introductionmentioning
confidence: 99%